1999
DOI: 10.1007/s004010051116
|View full text |Cite
|
Sign up to set email alerts
|

Variant Gerstmann-Sträussler syndrome with the P105L prion gene mutation: an unusual case with nigral degeneration and widespread neurofibrillary tangles

Abstract: We present here a case of variant Gerstmann-Sträussler syndrome (GSS) with a codon 105 mutation of the prion protein gene. A 57-year-old woman developed dementia and gait disturbance dissimilar to the spastic paraparesis that is observed in most cases with codon 105 mutation. The clinical course of the disease in this case was 12 years. The brain weighed 900 g, and the frontal lobe, pallidum and thalamus were markedly atrophic. Severe neuronal loss was observed in the deep layer of the frontal and temporal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…Whereas the emergence of infectious prion diseases is caused by toxic PrP conformers (PrP Sc ) that mediate the conversion of correctly folded PrP (PrP C ) molecules into the infectious form, familial prion diseases exhibit more diverged mechanisms of manifestation and clinical dynamics (reviewed in Aguzzi and Calella, 2009). Gerstmann-Sträussler-Scheinker syndrome (GSS) is a late-onset familial prion disorder that stems from the substitution of a proline at either residue P102 (Hsiao et al, 1989) or P105 (Yamazaki et al, 1999) in the sequence of PrP. Although the mechanism underlying GSS is poorly understood, we previously reported that these proline substitutions prevent PrP from folding properly, probably due to the abolishment of a chaperone-recognition site, leading to the misfolding and aggregation of PrP (Cohen and Taraboulos, 2003).…”
Section: Diseasesmentioning
confidence: 99%
“…Whereas the emergence of infectious prion diseases is caused by toxic PrP conformers (PrP Sc ) that mediate the conversion of correctly folded PrP (PrP C ) molecules into the infectious form, familial prion diseases exhibit more diverged mechanisms of manifestation and clinical dynamics (reviewed in Aguzzi and Calella, 2009). Gerstmann-Sträussler-Scheinker syndrome (GSS) is a late-onset familial prion disorder that stems from the substitution of a proline at either residue P102 (Hsiao et al, 1989) or P105 (Yamazaki et al, 1999) in the sequence of PrP. Although the mechanism underlying GSS is poorly understood, we previously reported that these proline substitutions prevent PrP from folding properly, probably due to the abolishment of a chaperone-recognition site, leading to the misfolding and aggregation of PrP (Cohen and Taraboulos, 2003).…”
Section: Diseasesmentioning
confidence: 99%
“…Some cases of diagnosed HD are actually caused by a mutation in the gene encoding PrP (PRNP) rather than any alteration to the huntingtin gene. 44,45 PRNP mutations can also be associated with some PD-like symptoms and neuropathology 46 and some demonstrate similarities to the tauopathies. 47 Collinge and colleagues described a kindred segregating pre-senile dementia, AD, HD, PD, Pick's disease, as well as prion disease (GerstmannStraussler-Scheinker syndrome and CJD).…”
Section: Introductionmentioning
confidence: 99%
“…This mutation was found in 5 GSS families, all from Japan [99][100][101][102][103][104][105][106]. The disease manifests as spastic paraparesis with brisk tendom reflexes and the presence of Babinski sign; in terminal stages, patients become teraplegic, demented, with tremor and limb rigidity.…”
Section: The Codon 105 Leu 129 Val Mutationmentioning
confidence: 99%